Decomposition of integrated high-density IoT data flow - Kuchuk, Heorhii; Kalinin, Yevhen; Dotsenko, Nataliia; Chumachenko, Igor; Pakhomov, Yuriy (Національний технічний університет "Харківський політехнічний інститут", 2024)
The concept of fog computing made it possible to transfer part of the data processing and storage tasks from the cloud to fog nodes to reduce latency. But in batch processing of integrated data streams from IoT sensors, it is sometimes necessary to distribute the tasks of the batch between the fog and cloud layers. For this, it is necessary to decompose the formed package. But the existing methods of decomposition do not meet the requirements for efficiency in high-density IoT systems. The subject of study in the article are methods of decomposition of integrated data streams. The purpose of the article is to develop a method of decomposition of an integrated data stream in a dense high-density Internet of Things fog environment. This will reduce the processing time of operational transactions.

Концепція туманних обчислень дозволила перенести частину завдань по обробці і зберіганню даних з хмари на туманні вузли для зниження затримки. Але при пакетній обробці інтегрованих потоків даних від сенсорів IoT іноді необхідно проводити розподіл завдань пакету між туманним і хмарним шарами. Для цього необхідно провести декомпозицію сформованого пакету. Але існуючі методи декомпозиції не відповідають вимогам по оперативності у системах Інтернету речей великої щільності. Предметом вивчення в статті є методи декомпозиції інтегрованих потоків даних. Метою статті є розробка методу декомпозиції інтегрованого потоку даних у туманному середовищі Інтернету речей великої щільності. Це дозволить зменшити час обробки оперативних транзакцій.
Декомпозиція інтегрованого потоку даних ІоТ великої щільності
Keywords: Internet of things; high density IoT; computer systems; cloud layers; stream processing; ІоТ великої щільності; Інтернет речей; комп'ютерні системи; туманні шари; потокова обробка; декомпозиція даних